Powder compact and method for producing the same, and method for producing powder magnetic core
By forming an insulating and conformal film on the surface of the soft magnetic powder, the adhesive strength is improved by using silane coupling agent, silicone resin and acrylic resin, which solves the problem that the powder-formed body is prone to defects or cracks under high pressure, and achieves a forming effect of uniform density and complete shape.
Patent Information
- Application Number
- CN202010650830.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-06
- Filing Date
- 2020-07-08
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2040-07-08
AI Technical Summary
During the powder pressing and forming process, due to insufficient adhesion between the soft magnetic powder, defects or cracks in the powder pressing molded body are easily caused. Especially when the pressing surface has a different step, uneven density leads to easy cracks in the boundary.
By forming an insulating film and a conformal film on the particle surface of the soft magnetic powder, the insulating film is made of a silane coupling agent and a silicone resin. The conformal film contains an acrylic resin with a glass transition point of less than 45 degrees, thereby improving the adhesion between the powders and suppressing the occurrence of defects or cracks.
It effectively improves the adhesion between soft magnetic powder, suppresses defects or cracks in the powder-pressed molded body, and ensures the density uniformity and shape integrity of the molded body.
Smart Images

Figure CN112542284B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a powder compact and a method for manufacturing the powder compact, and a method for manufacturing a powder magnetic core. Background Art
[0002] Reactors are used in various applications, such as drive systems of hybrid vehicles, electric vehicles, or fuel cell vehicles. As the core of the reactor, for example, a powder core is used. The powder core is formed by heat treating a powder compact. The powder compact is first subjected to an insulating film forming step of forming an insulating film on the surface of particles of a soft magnetic powder. Then, the powder compact is formed by compacting the soft magnetic powder having an insulating film formed on the surface of the particles.
[0003] [Prior art literature]
[0004] [Patent Document]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 2019-125622 Summary of the invention
[0006] [Problems to be solved by the invention]
[0007] During the press forming, the pressure was 10 ton / cm 2 ~20ton / cm 2 Therefore, if the bonding force between the soft magnetic powders is weak, the powder compact will be damaged or cracked. Depending on the situation, the legs of the powder compact may fall off completely, and the powder compact may not be formed into the desired shape. In particular, when the pressed surface of the powder compact has a step difference such as a bump, the density of the powder compact after the pressing will be uneven. Moreover, cracks are particularly likely to occur at the boundary between the low-density part and the high-density part of the powder compact.
[0008] The present invention is made to solve the above-mentioned problems, and its object is to provide a powder compact, a method for producing the powder compact, and a method for producing a powder core, which can improve the bonding strength between soft magnetic powders and suppress the occurrence of defects or cracks in the powder compact.
[0009] [Technical means to solve the problem]
[0010] The powder compact of the present invention comprises: soft magnetic powder; an insulating film covering the particle surface of the soft magnetic powder; and a conformal film covering the surface of the insulating film and containing an acrylic resin, wherein the glass transition point of the acrylic resin is 45 degrees or less.
[0011] In addition, the method for manufacturing a compressed powder molded body of the present invention includes: an insulating film forming step, forming an insulating film on the surface of soft magnetic powder particles; a conformal film forming step, adding an acrylic resin to the soft magnetic powder on which an insulating film is formed by the insulating film forming step, and coating the surface of the insulating film layer with the acrylic resin; and a molding step, pressurizing the soft magnetic powder that has passed the conformal film forming step, wherein the acrylic resin added in the conformal film forming step has a glass transition point of less than 45 degrees.
[0012] The method for manufacturing a powder compact of the present invention includes: an adding step of adding silicone resin and acrylic resin to a soft magnetic powder; a coating layer forming step of drying the soft magnetic powder that has passed the adding step to form a coating layer containing a mixture of silicone resin and acrylic resin; and a pressing step of pressurizing the soft magnetic powder that has passed the coating layer forming step.
[0013] Furthermore, a powder compact of the present invention includes: a soft magnetic powder; and a coating layer covering the soft magnetic powder, wherein the coating layer includes a mixture of a silicone resin and an acrylic resin.
[0014] [Effects of the Invention]
[0015] According to the present invention, it is possible to obtain a powder compact and a method for producing the powder compact, which can improve the binding force between soft magnetic powders and suppress the occurrence of defects or cracks in the powder compact. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 1 is a flowchart showing a method for producing a powder compact and a powder magnetic core according to an embodiment.
[0017] Figure 2 It is a schematic diagram showing the pressing direction in the press-forming step.
[0018] Figure 3 It is a schematic diagram showing the pressing direction in the press-forming step.
[0019] Figure 4 It is a schematic diagram showing the pressing direction in the press-forming step.
[0020] Figure 5 This is a graph showing the relationship between the glass transition point of acrylic resin and the grinding ratio.
[0021] Figure 6 This is a graph showing the relationship between the amount of acrylic resin added and the pulverization ratio in the second example.
[0022] Figure 7This is a graph showing the relationship between the amount of acrylic resin added and the pulverization ratio in the third example.
[0023] Figure 8 This is a graph showing the relationship between the amount of acrylic resin added and the iron loss in the third example.
[0024] Fig. 9 1 is a flowchart showing a method for producing a powder compact and a powder magnetic core according to the second embodiment.
[0025] Fig.10 This is a graph showing the relationship between the acrylic resin and the grinding ratio in Examples.
[0026] Fig.11 This is a graph showing the relationship between acrylic resin and iron loss in Examples.
[0027] Fig.12 This is a graph showing the relationship between the acrylic resin and the grinding ratio in Examples.
[0028] Fig.13 This is a graph showing the relationship between acrylic resin and iron loss in Examples. DETAILED DESCRIPTION
[0029] (First Embodiment)
[0030] The structure of the powder compact of the present embodiment is described. The powder compact of the present embodiment has a soft magnetic powder, an insulating coating and a conformal coating. The powder compact is formed by press-forming the soft magnetic powder covered by the insulating coating and the conformal coating. The powder compact is a compact before the heat treatment step of the step of manufacturing the powder core, and the powder core is formed by heat-treating the powder compact. The powder core can be used as the core of a reactor, for example. Furthermore, the powder compact of the present embodiment has a soft magnetic powder, an insulating coating and a conformal coating, but is not limited to this. For example, lubricants such as stearic acid and its metal salts and ethylene bisstearamide, ethylene bisstearamide, and ethylene bisstearic acid amide may be added.
[0031] Soft magnetic powder is a soft magnetic powder with iron as main component, and can use Fe powder, FeSi alloy powder, FeNi alloy powder, FeSiAl alloy powder (sendust), pure iron powder, amorphous alloy powder, nanocrystalline alloy powder or a mixed powder of these two or more powders etc.FeSiAl alloy powder, amorphous alloy powder or nanocrystalline alloy powder are particularly preferred.The shape retention of these powders is poor, so the effect of forming a shape-retaining film can be significantly obtained as in the present invention.Shape retention refers to the difficulty of pulverizing the pressed powder compact after compression molding, and by improving shape retention, the cracks generated in the pressed powder compact or the pressed powder compact can be suppressed from producing defects.
[0032] The insulating film is coated on the surface of the particles of the soft magnetic powder to provide insulation between the soft magnetic powder particles. The coating method includes coating the surface of each particle of the soft magnetic powder, coating the surface of a combined particle of several particles, and coating the entire surface of the particle or a part of the surface. In this embodiment, the insulating film is a mixed layer formed by mixing a silane coupling agent and a silicone resin.
[0033] As the silane coupling agent, for example, aminosilane-based, epoxysilane-based, isocyanurate-based, ethoxysilane-based, ethoxysilane-based, and methoxysilane-based agents can be used, and in particular, 3-aminopropyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, and tris-(3-trimethoxysilylpropyl)isocyanurate can be mentioned.
[0034] The amount of the silane coupling agent added is preferably 0.25 wt% to 1.0 wt% relative to the soft magnetic powder. By setting the amount of the silane coupling agent added within the above range, the fluidity of the soft magnetic powder can be improved, and the density, magnetic properties, and strength properties of the molded powder core can be improved.
[0035] Silicone resin is a resin having a siloxane bond (Si-O-Si) in the main skeleton. By using silicone resin, the flexibility of the insulating film is excellent. As silicone resin, methyl series, methylphenyl series, propylphenyl series, epoxy resin modified series, alkyd resin modified series, polyester resin modified series, rubber series, etc. can be used. Among them, in particular, when methylphenyl series silicone resin is used, the heat resistance of the insulating film is excellent.
[0036] The amount of silicone resin added to the soft magnetic powder is preferably 1.0 wt% to 2.0 wt%. If the amount added is less than 1.0 wt%, it will not function as an insulating film, and the magnetic properties will decrease due to increased eddy current loss. If the amount added is more than 2.0 wt%, the density of the powder core will decrease.
[0037] In this embodiment, the insulating film is a mixed layer formed by mixing a silane coupling agent and a silicone resin, but the insulating films may be formed separately without mixing. That is, a first insulating film may be formed by coating the surface of the particles of the soft magnetic powder with a silane coupling agent, and a second insulating film may be formed by coating the first insulating film with a silicone resin. In addition, the insulating film may be formed only with a silicone resin without using a silane coupling agent. Furthermore, the insulating film is not limited to a silane coupling agent or a silicone resin, and for example, a silicone oligomer or the like may be used as a well-known insulating film.
[0038] The conformal coating is coated on the surface of the insulating coating formed on the surface of the particles of the soft magnetic powder. The coating method includes the case where the soft magnetic powders formed with the insulating coating are coated one by one, and the case where several particles are coated on the combined particles. In addition, the conformal coating includes the case where the entire surface or a part of the surface is coated with the insulating coating. That is, the conformal coating does not need to completely cover the surface of the insulating coating, and also includes the case where it is attached to a part of the surface of the insulating coating. By forming the conformal coating, the conformality of the powder compact is improved. The conformal coating contains acrylic resin.
[0039] The amount of acrylic resin added is 0.5wt% or more and 1.5wt% or less relative to the soft magnetic powder. If the amount added is less than 0.5wt%, the effect of improving the shape retention is weak. On the other hand, if the amount added is more than 1.5wt%, the density of the powder compact is reduced and the iron loss is increased.
[0040] In addition, the glass transition point of the acrylic resin is preferably 45°C or less. By setting the glass transition point of the acrylic resin to 45°C or less, the shape retention can be improved. More preferably, the glass transition point of the acrylic resin is 33°C or less. By setting the glass transition point to 33°C or less, the shape retention can be further improved. Thus, the influence of the glass transition point Tg of the acrylic resin on the shape retention of the powder compact can be inferred as follows.
[0041] When the soft magnetic powder coated with acrylic resin is pressed and formed, the temperature rises compared to room temperature due to the friction heat of pressing. The greater the difference between the rising temperature and the glass transition point Tg of the acrylic resin, the easier it is for the acrylic resin to dissolve. By pressing and forming in a state where the acrylic resin is dissolved, the soft magnetic powder coated with the acrylic resin is more tightly bonded. Therefore, it is inferred that the adhesiveness of the soft magnetic powder of the acrylic resin with a lower glass transition point Tg is improved compared to the acrylic resin with a higher glass transition point Tg, and the crushing ratio can be reduced.
[0042] Furthermore, the glass transition point of the acrylic resin is preferably 15° C. or higher. If the glass transition point is 15° C. or lower, the acrylic resin will dissolve even at room temperature, and will dissolve immediately after the conformal film is formed before press molding, thereby reducing the fluidity of the soft magnetic powder. Therefore, it takes time to supply the soft magnetic powder with the conformal film formed thereon to the mold for press molding, and workability may deteriorate.
[0043] The conformal film may contain other additives as long as the main component is acrylic resin. Even if additives other than acrylic resin are added to the conformal film, the glass transition point of the acrylic resin may be 45° C. or lower.
[0044] Next, a method for producing a powder compact and a powder magnetic core according to the present embodiment will be described with reference to the drawings. Figure 1 FIG. 1 is a flow chart showing the steps for manufacturing the powder compact and the powder magnetic core according to the present embodiment. Figure 1 As shown, the method for manufacturing a powder compact and a powder magnetic core of the present embodiment includes: (1) an insulating film forming step, (2) a conformal film forming step, (3) a lubricant mixing step, (4) a compacting step, and (5) a heat treatment step.
[0045] (1) Insulation film forming step
[0046] The insulating film forming step is a step of forming an insulating film on the surface of the particles of the soft magnetic powder. In the insulating film forming step of the present embodiment, specifically, by adding a silane coupling agent and a silicone resin to the soft magnetic powder and mixing them, and drying them, an insulating film containing a mixture of a silane coupling agent and a silicone resin is formed on the surface of the particles of the soft magnetic powder. The drying temperature is preferably above 100°C and below 300°C. In addition, the drying time also varies depending on the drying temperature, for example, it is about 2 hours. Furthermore, in the method of adding the silane coupling agent and the silicone resin, the silane coupling agent and the silicone resin can be added to the soft magnetic powder after mixing, or the silane coupling agent can be first added to the soft magnetic powder, and then the silicone resin is added for mixing.
[0047] (2) Conformal film formation step
[0048] The conformal coating forming step is a step of coating the surface of the insulating coating with an acrylic resin. The conformal coating containing acrylic resin is formed on the surface of the insulating coating by mixing acrylic resin with the soft magnetic powder on which the insulating coating is formed and drying the mixture. The drying temperature is preferably 25°C to 150°C, and ideally 60°C to 150°C. The drying time also varies depending on the drying temperature, and is, for example, about 2 hours. By coating with a conformal coating containing acrylic resin, the bonding force between the powders is improved, and the conformal property is improved.
[0049] (3) Lubricant mixing step
[0050] The lubricant mixing step is a step of adding a lubricant to the soft magnetic powder coated with an acrylic resin and mixing the lubricant. As the lubricant, stearic acid and its metal salts and waxes such as ethylene bisstearamide, ethylene bisstearamide, and ethylene bisstearic acid amide can be used. The amount of lubricant added is preferably about 0.1wt% to 0.6wt% relative to the soft magnetic powder. By adding the lubricant, the sliding between the soft magnetic powders can be improved, thereby increasing the molding density. Furthermore, it is more preferred that the amount of lubricant added is about 0.2wt% to 0.5wt% relative to the soft magnetic powder. By setting it within the above range, the sliding between the soft magnetic powders can be further improved.
[0051] (4) Pressing step
[0052] In the pressing step, the soft magnetic powder with the insulating film and the conformal film is pressed to form a compact. The pressure during the pressing is 10 ton / cm 2 ~20ton / cm 2 , preferably an average of 12 ton / cm 2 ~15ton / cm 2 By going through this step, a powder compact is produced.
[0053] like Figure 2 As shown in FIG. 1 , the shape of the compact formed in this embodiment is a substantially E-shaped compact. Figure 2 As shown by the arrow, the powder compact is pressed in the same direction as the extension direction of the foot of the powder compact. That is, the pressing surface of the powder compact has a step difference. The step difference mentioned here refers to the concavity and convexity of the pressing surface, which refers to the degree of concavity and convexity to which the density of the convex parts (the parts with long lengths between the pressing surfaces) in the powder compact after pressing and molding becomes low, and the density of the concave parts (the parts with short lengths between the pressing surfaces) becomes high. In addition, the pressing surface is the end surface of the powder compact orthogonal to the pressing direction, and both the concave parts and the convex parts become the pressing surface.
[0054] When the pressed surfaces have a step difference, the short portion between the pressed surfaces becomes high density, and the long portion between the pressed surfaces tends to become low density. Therefore, cracks are likely to occur at the boundary between the low-density portion and the high-density portion.
[0055] However, in this embodiment, by adding 0.5wt% or more and 1.5wt% or less of acrylic resin, the bonding force between the powders can be increased. Therefore, the shape retention of the compact after compacting can be improved, and even if the compacting surface has a step difference, the generation of cracks in the compact after the compacting step can be suppressed.
[0056] Furthermore, in this embodiment, if Figure 2As shown in FIG. 1 , the pressing is performed in the same direction as the extending direction of the legs of the substantially E-shaped compact, but the pressing direction is not limited thereto. Figure 3 As shown, in the case of a substantially E-shaped powder compact in which the height of the middle leg is lower than the height of the outer leg, it is also possible to Figure 3 As shown by the arrow in FIG. 1 , the pressing is performed in a direction perpendicular to the extending direction of the leg of the powder compact. Even in the pressing direction, the pressing surface has a step difference. Figure 4 In the case of the so-called PQ type core shown in FIG. Figure 4 If the pressing is performed as shown by the arrow, there will be a step difference on the pressing surface. Figure 3 and Figure 4 In the case of general pressing, the shape retention is improved by forming a conformal film, thereby suppressing the generation of cracks in the powder compact.
[0057] (5) Heat treatment step
[0058] In the heat treatment step, the powder compact obtained through the compacting step is heat treated in N2 gas, N2+H2 gas non-oxidizing atmosphere or air at a temperature of 600°C or higher and below a temperature at which the insulating film covering the soft magnetic powder is destroyed (e.g., 900°C). By undergoing the heat treatment step, a powder magnetic core is manufactured.
[0059] (Second Embodiment)
[0060] (constitute)
[0061] The structure of the powder compact of the second embodiment is described. The powder compact of this embodiment includes soft magnetic powder, a coating layer and a lubricant. The coating layer covers the surface of the soft magnetic powder. The coating layer includes a mixture of silicone resin and acrylic resin. The lubricant covers the surface of the coating layer.
[0062] The powder compact is formed by pressing and compacting soft magnetic powder coated with a coating layer and a lubricant. The powder compact is a compact before the heat treatment step of the step of manufacturing a powder core, and the powder core is formed by heat treating the powder compact. The powder core can be used as a core of a reactor, for example.
[0063] Soft magnetic powder is a soft magnetic powder with iron as main component, and can use Fe powder, FeSi alloy powder, FeNi alloy powder, FeSiAl alloy powder (FeSiAl magnetic alloy), pure iron powder, amorphous alloy powder, nanocrystalline alloy powder or mixed powder of these two or more powders etc.FeSiAl alloy powder, amorphous alloy powder or nanocrystalline alloy powder are particularly preferred.The shape retention of these powders is poor, so the effect of the film layer that forms the mixture containing silicone resin and acrylic resin can be significantly obtained as the present invention.Shape retention refers to the difficulty of the crushing of the pressed powder compact after the compacting, and by improving shape retention, the crack produced in the pressed powder compact or the pressed powder compact can be suppressed to produce defect.
[0064] The coating layer covers the surface of the soft magnetic powder. The coating method includes coating the surface of each particle of the soft magnetic powder, coating the surface of a combined particle of several particles, and coating the entire surface of the particle or a part of the surface. In other words, the coating layer does not need to completely cover the surface of the soft magnetic powder, and may be attached to a part of the surface of the soft magnetic powder.
[0065] The coating layer is a mixed layer containing a mixture of silicone resin and acrylic resin. The coating layer of this embodiment is a mixed layer formed by mixing a silane coupling agent, a silicone resin and an acrylic resin. That is, if the coating layer contains silicone resin and acrylic resin, other materials may also be mixed. In this embodiment, the silicone resin and the silane coupling agent function as an insulating coating.
[0066] The amount of acrylic resin added is preferably 0.2wt% or more and 0.5wt% or less relative to the soft magnetic powder. If the amount added is less than 0.2wt%, the effect of improving the shape retention is weak. On the other hand, if the amount added is more than 0.5wt%, it will lead to an increase in iron loss or a decrease in initial magnetic permeability. As in the present embodiment, by forming a coating layer, as shown in the examples described later, the shape retention can be improved while reducing the amount of acrylic resin added.
[0067] In this embodiment, the coating layer covers the surface of the soft magnetic powder, but the present invention is not limited thereto. For example, an insulating coating layer made of silicone oligomer or the like may be formed on the surface of the soft magnetic powder, and then the coating layer may be formed to cover the surface of the insulating coating layer.
[0068] (Manufacturing method)
[0069] Next, a method for producing the powder compact and the powder magnetic core will be described. Fig. 9 FIG. 1 is a flow chart showing the steps for manufacturing the powder compact and the powder magnetic core according to the present embodiment. Fig. 9As shown, the method for manufacturing the powder compact and the powder magnetic core of the present embodiment includes: (1) an adding step, (2) a film layer forming step, (3) a lubricant mixing step, (4) a pressing step, and (5) a heat treatment step. The (4) pressing step and the (5) heat treatment step are the same as those of the first embodiment, and therefore their description is omitted.
[0070] (1) Add steps
[0071] The adding step is a step of adding silicone resin and acrylic resin to the soft magnetic powder. In the present embodiment, the silane coupling agent, silicone resin, and acrylic resin are added in the order of each other and mixed. The acrylic resin is preferably added by dissolving in an organic solvent. The case where the acrylic resin is dissolved in an organic solvent and added can significantly improve the shape retention. Although it is a speculation but not limited to this, in the case of adding the acrylic resin of the water-soluble emulsion described later, the acrylic resin is contained in a powder state, so it is difficult to disperse, and the acrylic resin is difficult to evenly adhere to the soft magnetic powder. On the other hand, in the case of adding the acrylic resin by dissolving in an organic solvent, since the acrylic resin is dissolved in the organic solvent, the acrylic resin is easily evenly attached to the soft magnetic powder. Therefore, it is speculated that the case where the acrylic resin is dissolved in an organic solvent and added can improve the shape retention. As organic solvents, acetone, toluene, xylene, etc. can be listed.
[0072] In this embodiment, the silane coupling agent, silicone resin, and acrylic resin are added to the soft magnetic powder in this order, but the acrylic resin can also be added at the same time as the silicone resin. The acrylic resin is preferably added immediately after the silicone resin is added or added at the same time as the silicone resin. By adding the acrylic resin at the above time, the acrylic resin can be evenly attached to the soft magnetic powder, thereby further improving the shape retention. Furthermore, it is not preferred to add after pre-mixing the silicone resin and the acrylic resin. The reason is that if mixed first, the silicone resin reacts with the acrylic resin before being added to the soft magnetic powder, and it may not be possible to make the acrylic resin evenly attached to the soft magnetic powder.
[0073] (2) Film layer formation step
[0074] The step of forming a film layer is a step of drying the silane coupling agent, silicone resin and acrylic resin added and mixed in the adding step to form a film layer. That is, the silane coupling agent, silicone resin and acrylic resin are dried at the same time. Therefore, compared with the case where each material is dried, the step of drying can be reduced. Therefore, the productivity of the powder compact and the powder magnetic core can be improved, and cost reduction can be sought. The drying temperature is preferably 100° C. or more and 200° C. or less. The drying time also varies depending on the drying temperature, for example, 2 hours.
[0075] (3) Lubricant mixing step
[0076] The lubricant mixing step is a step of adding a lubricant to the soft magnetic powder coated with the film layer and mixing the lubricant. By mixing the lubricant, the sliding between the powders can be improved, thereby increasing the molding density. Furthermore, the punching pressure of the upper punch during molding can be reduced, and the longitudinal lines on the core wall surface caused by the contact between the mold and the powder can be prevented.
[0077] Furthermore, when forming the insulating film layer, before the addition step, silicone oligomer is added to the soft magnetic powder, mixed and dried. The drying temperature is preferably 25°C to 350°C, and the drying time also depends on the drying temperature, for example, 2 hours. Thus, an insulating film layer is formed on the surface of the soft magnetic powder. After the above steps, the steps after the addition step are performed in sequence.
[0078] (First embodiment)
[0079] (Comparison of glass transition point Tg of acrylic resin)
[0080] The first example is described below. In the first example, the type of acrylic resin used as the conformal coating was changed to produce powder compacts as samples. The powder compacts were produced in the following manner.
[0081] (1) Insulation film forming step
[0082] 0.5 wt% of silane coupling agent and 1.5 wt% of silicone resin were mixed with FeSiAl alloy powder having an average particle size (median particle size (D50)) of 25 μm, and then dried at a drying temperature of 150°C for 2 hours and passed through a sieve with a mesh size of 250 μm to eliminate agglomeration.
[0083] (2) Conformal film formation step
[0084] The FeSiAl alloy powder coated with the silane coupling agent and the silicone resin in the insulating film forming step was mixed with 0.50 wt% of the five acrylic resins A to E shown in Table 1. Thereafter, the powder was dried at 110°C for 2 hours and passed through a sieve with a mesh size of 250 μm to eliminate aggregation.
[0085] [Table 1]
[0086] type Non-volatile components (wt%) Glass transition point Tg(℃) A 40 45 B 55 6 C 40 33 D 40 15 E 50 20
[0087] (3) Lubricant mixing step
[0088] 0.4 wt % of a powdered lubricant (Acrawax (registered trademark)) was added to the FeSiAl alloy powder further coated with the acrylic resin in the conformal film forming step and mixed.
[0089] (4) Pressing
[0090] The FeSiAl alloy powder after the lubricant mixing step was pressed and compacted using a mold at room temperature to obtain powder compacts with an outer diameter of 16.5 mm, an inner diameter of 11.0 mm, and a height of 5.0 mm. The pressure of the pressing was 15 ton / cm 2 conduct.
[0091] The weight and crushing amount of each powder compact produced in the above manner are measured. The weight of the powder compact is the weight after compacting. In the present embodiment, it is the total weight of the soft magnetic powder, insulating coating, conformal coating and lubricant. The crushing amount is measured by placing the powder compact on a sieve with a mesh size of 850 μm using a vibrating sifter (KFC-500-1DC). The powder compact is placed on a sieve with a mesh size of 850 μm, and the weight falling under the sieve is measured while vibrating it for 30 seconds. A scale (ASPRO ASP123F) is used to measure the weight and crushing amount of the powder compact. The vibration is carried out under the conditions of a motor (200 V, 0.4 kW) and a frequency (50 Hz).
[0092] The results of the weight and crushing amount of each powder compact are shown in Table 2 and Figure 5 shown. Figure 5 This is a graph showing the relationship between the glass transition point Tg of acrylic resin and the grinding ratio.
[0093] [Table 2]
[0094]
[0095] The "density" shown in Table 2 is the apparent density. That is, the outer diameter, inner diameter and height of the produced powder compact were measured, and these values were combined based on π×(outer diameter 2 -Inner diameter 2 )×height to calculate the volume (cm 3 ). Then, the weight of each powder compact was measured, and the density was calculated by dividing the measured weight by the calculated volume.
[0096] As shown in Table 2 and Figure 5As shown, the crushing ratio is high for those with a high glass transition point Tg, and the crushing ratio tends to decrease as the glass transition point Tg decreases. In Example 1, where the glass transition point Tg is the highest at 45°C, it is shown that the crushing ratio is also much lower than 10%, which can improve the shape retention and suppress cracks or defects in the powder compact. In particular, if Example 3 with a glass transition point Tg of 33°C is compared with Example 1 with a glass transition point Tg of 45°C, it can be seen that the crushing ratio of Example 3 is greatly reduced compared to Example 1, and the shape retention is improved. Therefore, the glass transition point Tg of the acrylic resin is more preferably below 33°C.
[0097] (Second embodiment)
[0098] (Comparison based on the amount of acrylic resin added)
[0099] The second embodiment is described. In the second embodiment, only the acrylic resin A shown in Table 1 is used as the conformal coating, and the amount of acrylic resin A added is changed to produce a powder compact. The amount of acrylic resin added is set to 0.00wt% to 2.00wt% as shown in Table 3. The method for producing the powder compact is the same as that of the first embodiment. Then, the weight and the crushing amount of the powder compact are measured by the same method as that of the first embodiment.
[0100] The measurement results of the second embodiment are shown in Table 3 and Figure 6 shown. Figure 6 This is a graph showing the relationship between the amount of acrylic resin added and the grinding ratio in this example.
[0101] [Table 3]
[0102]
[0103] As shown in Table 3 and Figure 6 As shown, the crushing amount of Comparative Example 1 without adding acrylic resin and Comparative Example 2 with adding 0.25wt% acrylic resin is more than double the crushing amount of Example 1, and the crushing ratio is also increased to more than 10%. On the other hand, the crushing ratio of Example 1, Examples 6 to 8, and Comparative Example 3 with adding more than 0.5wt% acrylic resin is less than 10%, and the crushing amount is small. Therefore, when the addition amount of acrylic resin is 0.5wt% or more, the shape retention of the powder compact can be improved.
[0104] Particular attention should be paid to the aspect of increasing the density of the powder compact by adding a certain amount of acrylic resin. As can be seen from Table 3, the density increases from Comparative Example 1 where no acrylic resin is added to Example 7 where 1.00 wt% is added, and decreases when more than 1.00 wt% is added.
[0105] Generally, it is said that the density decreases when a resin is added. However, when a certain amount of acrylic resin is added, the powder coated with the acrylic resin is further bonded and combined, so it is estimated that the density increases.
[0106] However, the density of Comparative Example 3 to which 2.00wt% of acrylic resin was added was lower than that of Comparative Example 1 to which no acrylic resin was added. It is speculated that the density is reduced due to the rebound of the acrylic resin. That is, since the acrylic resin has elasticity, when the powder compact is punched out from the mold after compression molding, if it wants to return to its original shape, rebound will occur. Due to the rebound, the powder combined by compression molding is separated and the density is reduced. Moreover, the more the amount of acrylic resin added, the greater the rebound force. Therefore, it is considered that the density of Comparative Example 3 to which 2.00wt% of acrylic resin was added is reduced. According to the above aspects, by setting the amount of acrylic resin added to 0.5wt% or more and 1.5wt% or less, the density can be increased while improving the shape retention of the powder compact.
[0107] (Third Embodiment)
[0108] (Comparison of the amount of acrylic resin added and iron loss)
[0109] In the third embodiment, the acrylic resin C shown in Table 1 is used as a conformal coating to produce a powder compact. The amount of acrylic resin added is set to 0.00wt% to 3.00wt% as shown in Table 4. In addition, the soft magnetic powder used in the third embodiment uses FeSiAl alloy powder with an average particle size (median particle size (D50)) of 19μm. The method for producing the powder compact as a sample is the same as that of the first embodiment.
[0110] In the third embodiment, in addition to measuring the weight and crushing amount of the powder compact using the same method as the first embodiment, the iron loss Pcv and the magnetic permeability μ are also measured. The measurement conditions of the magnetic permeability and iron loss are set to a frequency of 100kHz and a maximum magnetic flux density Bm=100mT. Regarding the iron loss, a winding with 17 turns of the primary winding and 17 turns of the secondary winding is wound with a copper wire of φ0.5mm, and the calculation is performed using a BH analyzer (Yantong Measurement Co., Ltd.: SY-8219) as a magnetic measurement device. The calculation is performed using the following (1) to (3) formulas and the least squares method to calculate the hysteresis loss coefficient and the eddy current loss coefficient for the frequency curve of the iron loss.
[0111] Pcv=Kh×f+Ke×f 2 …(1)
[0112] Ph=Kh×f…(2)
[0113] Pe=Ke×f 2 …(3)
[0114] Pcv: Iron loss
[0115] Kh: Hysteresis loss coefficient
[0116] Ke: Eddy current loss coefficient
[0117] f: frequency
[0118] Ph: Hysteresis loss
[0119] Pe: Eddy current loss
[0120] The magnetic permeability is set as the amplitude magnetic permeability when the maximum magnetic flux density Bm is set during the iron loss Pcv measurement, and is calculated using an inductance capacitance resistance (LCR) meter (manufactured by Agilent Technologies, Inc.: 4284A). Furthermore, "μ0" shown in the following Table 4 represents the initial magnetic permeability when no DC is superimposed, that is, the magnetic field strength is 0H (A / m). "μ12k" in Table 4 represents the magnetic permeability when the magnetic field strength is 12kH (A / m).
[0121] The measurement results of the third embodiment are shown in Table 4 and Figure 7 , Figure 8 shown. Figure 7 This is a graph showing the amount of acrylic resin added and the grinding ratio in this example. Figure 8 This is a graph showing the relationship between the amount of acrylic resin added and the iron loss.
[0122] [Table 4]
[0123]
[0124] As shown in Table 4 and Figure 7 As shown in Figure 2, the more the amount of acrylic resin added increases, the lower the crushing ratio. On the other hand, if we focus on the iron loss, Figure 8 As shown in FIG. 1 , the iron loss increases as the amount of acrylic resin added increases. In particular, the iron loss of Example 12 in which 1.50 wt% of acrylic resin was added remained at 277 (kw / m 3 ), but the iron loss of Comparative Example 5 with 2.00wt% added is 329 (kw / m 3 ), the difference is 50(kw / m 3 Therefore, by setting the addition amount of acrylic resin to 1.50wt% or less, good iron loss characteristics can be maintained.
[0125] (Fourth embodiment)
[0126] Next, examples will be described. Examples 13, 14, and Comparative Examples 7 to 10 as samples were prepared as follows.
[0127] (Example 13 and Example 14)
[0128] (1) Samples of Examples 13 and 14 were prepared as follows. As described below, Examples 13 and 14 differed only in the amount of acrylic resin added.
[0129] FeSiAl alloy powder having an average particle size (median particle size (D50)) of 24.5 μm produced by gas atomization was prepared, and 0.5 wt % of a silane coupling agent, 1.5 wt % of a silicone resin, and a water-soluble emulsion acrylic resin were sequentially added to the FeSiAl alloy powder and mixed.
[0130] The amount of acrylic resin added is shown in Table 5, which is 0.25 wt% in Example 13 and 0.50 wt% in Example 14. The amount of acrylic resin added shown in Table 5 is the amount of acrylic resin added to the soft magnetic powder. In addition, the acrylic resin of the water-soluble emulsion means that the acrylic resin powder is dispersed in a water solution in a powder state equal to the amount of acrylic resin added.
[0131] (2) The FeSiAl alloy powder to which the silane coupling agent, the silicone resin, and the acrylic resin were added and mixed was dried at a drying temperature of 150° C. for 2 hours to form a coating layer.
[0132] (3) In order to eliminate agglomeration, the FeSiAl alloy powder forming the coating layer was passed through a sieve with a mesh size of 250 μm. Then, 0.4 wt% of a lubricant (Acrawax (registered trademark)) was added.
[0133] (4) The FeSiAl alloy powder with lubricant added was filled into a mold and pressed to obtain powder compacts with an outer diameter of 16.5 mm, an inner diameter of 11.0 mm, and a height of 5.0 mm. The pressing pressure was 15 ton / cm 2 conduct.
[0134] (Comparative Examples 7 to 10)
[0135] The samples of Comparative Examples 7 to 10 were prepared as follows. As shown below, Comparative Examples 7 to 10 differed only in the amount of acrylic resin added. In addition, Comparative Examples 7 to 10 differed from Examples 13 and 14 in that a silane coupling agent and a silicone resin were added, dried, and then acrylic resin was added and dried.
[0136] A FeSiAl alloy powder having an average particle size (median particle size (D50)) of 24.5 μm was prepared by gas atomization. 0.5 wt% of a silane coupling agent and 1.5 wt% of a silicone resin were added to the FeSiAl alloy powder in sequence and mixed. The powder was then dried at a drying temperature of 150° C. for 2 hours to form a mixed layer of the silane coupling agent and the silicone resin on the surface of the FeSiAl alloy powder.
[0137] In order to eliminate the agglomeration of the FeSiAl alloy powder forming the mixed layer, the powder was passed through a sieve with a mesh size of 250 μm, and then, the acrylic resin of the water-soluble emulsion in each addition amount shown in Table 5 was added and mixed. The method for preparing the acrylic resin of the water-soluble emulsion is the same as that in the embodiment. The FeSiAl alloy powder to which the acrylic resin was added was dried at a drying temperature of 110°C for 2 hours to form an acrylic resin layer on the surface of the mixed layer. That is, in Comparative Examples 8 to 10, a two-layer structure of a mixed layer and an acrylic resin layer was formed. Furthermore, Comparative Example 7, to which no acrylic resin was added, did not perform this step, and only formed a mixed layer.
[0138] Afterwards, the mixture was passed through a sieve with a mesh size of 250 μm to eliminate agglomeration. Then, a lubricant (Acrawax (registered trademark)) was added and compacted to produce a powder compact. The amount of lubricant added, the pressure during compacting, and the size of the powder compact were the same as those in the manufacturing steps (3) and (4) of Examples 13 and 14.
[0139] The weight, crushing amount and height of each powder compact produced as described above are measured. The height of the powder compact is the height of the powder compact after compression molding. The weight of the powder compact is the weight after compression molding. In this embodiment, it is the total weight of the soft magnetic powder, silane coupling agent, silicone resin, acrylic resin and lubricant. The crushing amount is measured by placing the powder compact on a sieve with a mesh of 850μm using a vibrating sifter (KFC-500-1DC), and vibrating it for 30 seconds to measure the weight that falls under the sieve. A scale (AS PROASP123F) was used to measure the weight and crushing amount of the powder compact. The vibration was carried out under the conditions of a motor (200V, 0.4kW) and a frequency (50Hz).
[0140] In addition, the powder compacts of Example 13, Example 14, and Comparative Examples 7 to 10 were integrally produced and heat treated at 700°C for 2 hours to produce powder cores. A winding of 17 turns of primary winding and 17 turns of secondary winding was wound on the powder core using a φ0.5 mm copper wire, and the iron loss and magnetic permeability were measured. The measurement conditions of magnetic permeability and iron loss were set to a frequency of 100 kHz and a maximum magnetic flux density Bm = 100 mT.
[0141] The iron loss was calculated using a BH analyzer (SY-8219, Iwatsu Measurement Co., Ltd.) as a magnetic measurement device. The calculation was performed by calculating the hysteresis loss coefficient and the eddy current loss coefficient from the frequency curve of the iron loss using the following equations (1) to (3) by the least square method.
[0142] Pcv=Kh×f+Ke×f 2 …(1)
[0143] Ph=Kh×f…(2)
[0144] Pe=Ke×f 2 …(3)
[0145] Pcv: Iron loss
[0146] Kh: Hysteresis loss coefficient
[0147] Ke: Eddy current loss coefficient
[0148] f: frequency
[0149] Ph: Hysteresis loss
[0150] Pe: Eddy current loss
[0151] The magnetic permeability is set as the amplitude magnetic permeability when the maximum magnetic flux density Bm is set when measuring the iron loss, and is calculated using an LCR meter (manufactured by Agilent Technologies, Inc.: 4284A). Furthermore, "μ0" shown in the following Table 5 represents the initial magnetic permeability when no DC is superimposed, that is, the magnetic field strength is 0H (A / m). "μ10k" in Table 5 represents the magnetic permeability when the magnetic field strength is 10kH (A / m).
[0152] The above test results are shown in Table 5 and Fig.10 , Fig.11 shown. Fig.10 This is a graph showing the relationship between the amount of acrylic resin added and the grinding ratio. Fig.11 This is a graph showing the relationship between the amount of acrylic resin added and the iron loss.
[0153] [Table 5]
[0154]
[0155] The "density" shown in Table 5 is the apparent density. That is, the outer diameter, inner diameter and height of the produced powder compact were measured, and these values were used based on π×(outer diameter 2 -Inner diameter 2 )×height to calculate the volume (cm 3). Then, the weight of each powder compact is measured, and the density is calculated by dividing the measured weight by the calculated volume. In addition, the compact height is the height of the powder compact measured after compression molding.
[0156] As shown in Table 5 and Fig.10 As shown, Examples 13 and 14, in which a coating layer was formed on the surface of the FeSiAl alloy powder, had a much lower grinding ratio than Comparative Example 7, in which no acrylic resin was added. This confirmed that the addition of acrylic resin can improve the shape retention.
[0157] In addition, when Example 13 and Comparative Example 8 are compared in which the amount of acrylic resin added is the same, the crushing ratio of Example 13 is 2.0%, while the crushing ratio of Comparative Example 8 is 6.9%, and the crushing ratio of Example 13 is less than one-third of that of Comparative Example 8. When Example 14 is compared with Comparative Example 9, the crushing ratio of Example 14 is 1.1%, while the crushing ratio of Comparative Example 9 is 4.8%, and the crushing ratio of Example 14 is less than one-quarter of that of Comparative Example 9, which is very small. This shows that the case where the silane coupling agent, silicone resin, and acrylic resin are dried simultaneously to form a film layer can improve shape retention, compared with the case where the silane coupling agent and silicone resin are dried and then the acrylic resin is added and dried.
[0158] Moreover, as shown in Table 5 and Fig.11 As shown, the iron loss of Examples 13 and 14 is lower than that of Comparative Examples 7 to 10. The iron loss of Example 14, which has the highest iron loss among the examples, is also 331 (kw / m 3 ), maintaining a better value than Comparative Example 9, which has the lowest iron loss among the comparative examples. This is because, as in the examples, by forming a coating layer on the surface of the FeSiAl alloy powder, the fluidity of the FeSiAl alloy powder can be further improved, so that a high-density powder compact can be produced. Therefore, the hysteresis loss can be reduced, and as a result, the iron loss can be reduced.
[0159] However, when comparing Example 13 with Example 14, if the amount of acrylic resin added is increased, the iron loss increases and the initial magnetic permeability decreases. Therefore, if more than 0.5wt% of acrylic resin is added, a further increase in iron loss and a decrease in initial magnetic permeability can be expected. Therefore, by setting the upper limit of the amount of acrylic resin added to 0.5wt% relative to the soft magnetic powder, the shape retention can be improved and good magnetic properties can be obtained.
[0160] Next, powder compacts of Examples 15 to 17 and Comparative Examples 11 to 14 were produced as follows.
[0161] (Example 15 to Example 17)
[0162] The samples of Examples 15 to 17 were prepared as follows. As shown below, Examples 15 to 17 differed only in the amount of acrylic resin added.
[0163] FeSiAl alloy powder having an average particle size (median particle size (D50)) of 19.5 μm produced by gas atomization was prepared, and 0.5 wt % of a silane coupling agent, 1.5 wt % of a silicone resin, and an acrylic resin dissolved in an organic solvent were sequentially added to the FeSiAl alloy powder and mixed.
[0164] Acetone was used as the organic solvent. The amount of acetone added was set to 1.0 wt% relative to the FeSiAl alloy powder, and the acrylic resins added in the amounts shown in Table 6 were dissolved in acetone. Then, the steps of manufacturing step (2), manufacturing step (3), and manufacturing step (4) of Example 13 and Example 14 were sequentially performed to produce a powder compact.
[0165] (Comparative Example 11 to Comparative Example 14)
[0166] A FeSiAl alloy powder having an average particle size (median particle size (D50)) of 19.5 μm was prepared by a gas atomization method. 0.5 wt% of a silane coupling agent and 1.5 wt% of a silicone resin were added to the FeSiAl alloy powder in sequence and mixed. Then, the powder was dried at a drying temperature of 150° C. for 2 hours to form a mixed layer of the silane coupling agent and the silicone resin on the surface of the FeSiAl alloy powder.
[0167] In order to eliminate the aggregation of the FeSiAl alloy powder formed with the mixed layer, the powder was passed through a sieve with a mesh size of 250 μm, and then, in the same manner as in Examples 15 to 17, acrylic resins in various amounts shown in Table 6 were dissolved in acetone as an organic solvent, and acrylic resins were added. The FeSiAl alloy powder to which the acrylic resin was added was dried at a drying temperature of 130° C. for 2 hours to form an acrylic resin layer on the surface of the mixed layer. The subsequent steps were carried out in the same manner as in Comparative Examples 7 to 10 to produce a powder compact.
[0168] The weight, crushing amount and height of each powder compact produced in the above manner were measured. In addition, the powder compacts of Examples 15 to 17 and Comparative Examples 11 to 14 were produced in one piece, and heat treated at 700°C for 2 hours to produce a powder core. A winding of 17 turns of primary winding and 17 turns of secondary winding was wound on the powder core using a φ0.5 mm copper wire, and the iron loss and magnetic permeability were measured. The measuring device or measuring conditions were the same as described above.
[0169] The results are shown in Table 6 and Fig.12 , Fig.13 shown. Fig.12 This is a graph showing the relationship between the amount of acrylic resin added and the grinding ratio. Fig.13 This is a graph showing the relationship between the amount of acrylic resin added and the iron loss.
[0170] [Table 6]
[0171]
[0172] When comparing Example 17 and Comparative Example 13, which have the same amount of acrylic resin added, the crushing ratio of Example 17 is 1.6%, while the crushing ratio of Comparative Example 13 is 14.7%. The crushing ratio of Example 17 is only about one ninth of that of Comparative Example 13, which is extremely small. In addition, the crushing ratios of Examples 15 and 16, which have less acrylic resin added than Example 17, are also less than that of Comparative Example 13. That is, the Examples can improve the shape retention with a smaller amount of acrylic resin added.
[0173] In addition, in the examples in which the coating layer was formed on the surface of the FeSiAl alloy powder, the pulverization ratio of Example 15 in which 0.10 wt% of acrylic resin was added was 6.9%. On the other hand, the pulverization ratio of Example 16 in which 0.20 wt% of acrylic resin was added was 2.7%. Thus, it was confirmed that the addition of 0.2 wt% or more of acrylic resin further improved the shape retention.
[0174] Furthermore, as shown in Table 5, when the acrylic resin of the water-soluble emulsion is the same in Example 14 and Comparative Example 9, the crushing ratio of Example 14 is 1.1%, while that of Comparative Example 9 is 4.8%, and the crushing ratio of Example 14 is about one-fourth of that of Comparative Example 9. On the other hand, when Example 17 and Comparative Example 13 are compared, in which the same amount of acrylic resin is dissolved and added using an organic solvent such as acetone, the crushing ratio of Example 17 is about one-ninth of that of Comparative Example 13 as described above. That is, the crushing ratio can be greatly reduced when the acrylic resin is dissolved in acetone as an organic solvent and added, compared with the comparative example. It is thus confirmed that the shape retention is further improved when the acrylic resin is dissolved in an organic solvent and added.
[0175] (Other embodiments)
[0176] In this specification, although the embodiments of the present invention are described, the embodiments are presented as examples and are not intended to limit the scope of the invention. The embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the scope of the invention. The embodiments or their modifications are included in the scope or gist of the invention, and are also included in the invention described in the claims and their equivalents.
Claims
1. A powder compact, characterized in that: include: Soft magnetic powder; An insulating film covering the particle surface of the soft magnetic powder; as well as a conformal film covering the surface of the insulating film and comprising an acrylic resin, The glass transition point of the acrylic resin is 15 degrees or more and 45 degrees or less, The acrylic resin is added in an amount of 0.5 wt % or more and 1.5 wt % or less relative to the soft magnetic powder.
2. The powder compact according to claim 1, wherein: The acrylic resin has a glass transition point of 15 degrees or more and 33 degrees or less.
3. The powder compact according to claim 1 or 2, characterized in that: Including the end surface that is pressed during press forming, i.e., the pressed surface, The pressing surface has a step difference.
4. The powder compact according to claim 1 or 2, characterized in that: The soft magnetic powder is amorphous soft magnetic powder, FeSiAl alloy or nanocrystalline alloy.
5. The powder compact according to claim 1 or 2, characterized in that: When the compact is placed on a sieve with an opening of 850 μm and vibration is applied for 30 seconds, the ratio of the weight of the crushed compact to the weight of the compact is 6.7% or less.
6. A method for producing a powder compact, characterized in that: include: An insulating film forming step of forming an insulating film on the surface of the soft magnetic powder particles; a conformal coating forming step of adding an acrylic resin to the soft magnetic powder on which the insulating coating is formed in the insulating coating forming step, and coating the surface of the insulating coating with the acrylic resin; and a molding step of press-molding the soft magnetic powder after the conformal coating forming step; The acrylic resin added in the conformal film forming step has a glass transition point of 15 degrees or more and 45 degrees or less, The acrylic resin is added in an amount of 0.5 wt % or more and 1.5 wt % or less relative to the soft magnetic powder.
7. A method for producing a powder compact, characterized in that: include: An adding step of adding silicone resin and acrylic resin to the soft magnetic powder; a coating layer forming step of drying the soft magnetic powder after the adding step to form a coating layer containing a mixture of a silicone resin and an acrylic resin; as well as a pressing step of pressing and molding the soft magnetic powder after the film layer forming step; and The acrylic resin is added in an amount of 0.2 wt % or more and 0.5 wt % or less relative to the soft magnetic powder.
8. The method for producing a powder compact according to claim 7, wherein: The acrylic resin is added by being dissolved in an organic solvent.
9. The method for producing a powder compact according to claim 7 or 8, characterized in that: The soft magnetic powder is amorphous soft magnetic powder, FeSiAl alloy or nanocrystalline alloy.
10. A method for manufacturing a powder magnetic core, characterized in that: The method comprises a heat treatment step of heat-treating the powder compact produced by the production method according to any one of claims 6 to 9.
11. A powder compact, characterized in that: include: Soft magnetic powder; as well as a coating layer covering the soft magnetic powder, The film layer comprises a mixture of silicone resin and acrylic resin, and The acrylic resin is added in an amount of 0.2 wt % or more and 0.5 wt % or less relative to the soft magnetic powder.
Citation Information
Patent Citations
Method for manufacturing powder-compact magnetic core
JP2019125622A
Composite magnetic material and its manufacturing method
JP2003347113A
Coil component and power supply device using it
JP2004253434A
Powder magnetic core and production method for same
US20140232507A1